Environmental Health Risk Factor in the Community Around of Rejo Agung Baru Sugar Factory Madiun - Inta Hestya; Corie Indria Prasasti (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract:  Emissions of dust  particles  (baggase and  charcoal)  into the  air by a sugar  factory  in the  production was pollution  to the  environment that need to be  watched. These pollutants  materials  get  into the  house through vents or open doors.  The  purpose of this research was  to describe the  risk factor of environmental health  relation to the amount  of risk exposure PM2,5, the community behaviour  and  home condition. This research is descriptive research with cross sectional design and  the number of samples 14 housewife. Data was  collected is PM2,5  levels  in a room (analyzed with environmental health risk assessment), weight,  behavior  of respondents and the condition of the house. The results  showed there were  3 people respondents at risk of unsafe exposure to PM2,5  weight  and concentration by long in the home 24 hours/day and exposure of 350 days/year for 30 years. Risk factors of behavior related to the habit of smoking family members and the use  of insect repellent fuel, while environmental factors  (condition of the house) was temperature, humidity and the distance of the house from the sugar factory. Concluded that the respondents have a risk of unsafe exposure to PM2,5  was  the respondent with a distance of home < 300 meters, have  family members who smoke, use insect repellent  and fuel temperature and humidity  were  not eligible. Required increased awareness of family members of the respondents not to smoke in the house, do  not use  insect repellent  and  maximize existin ventilation function.Keywords: Environmental  Health Risk Assessment, PM2,5, behavior  community, home condition, sugar factor